Influence of HKUST-1 and emeraldine based on the long-term stability of emeraldine salt-coated SP-POF for room temperature optical NH3 gas sensing - Ismail, Abdul Hadi; Yaacob, Mohd Hanif; Mahdi, Mohd Adzir; Sulaiman, Yusran (Elsevier, 2022)
A long-term sensitivity performance of conducting polymers and metal-organic frameworks coated on side-polished plastic optical fibre (SP-POF) was presented. SP-POF is an excellent option for potential long-distance and remote gas sensing and monitoring application. The presence of functional groups, porosity and surface area of the active materials were validated by Raman, Fourier transform infrared (FT-IR), X-Ray diffraction (XRD) and BET analyses. The sole copper-based metal-organic framework (HKUST-1)-coated SP-POF exhibited a good sensitivity (0.83/vol%) with a response time of 1.54 min. Further, the influence of acid dopants and oxidants on the optical response of doped-polyaniline (the emeraldine salt, ES) to 1% ammonia (NH3) gas was also optimised. Significant influence of HKUST-1 and emeraldine base (EB) on long-term optical NH3 sensitivity of emeraldine salt (ES)-coated SP-POF were related to NH3 desorption rate and affinity of the materials towards atmospheric vapour. ES-EB composite has exhibited higher NH3 sensitivity to the sole ES and ES-(HKUST-1) with minimal loss of sensitivity to a set of high NH3 gas concentrations over 70 days. ES-EB coated SP-POF has exhibited minimal sensitivity loss to NH3 gas throughout the test duration with a 7.8% decrease followed by ES (28.1%) and ES-(HKUST-1) (50.86%). Development of SP-POF coated with ES-EB composite is a viable approach to retain good optical NH3 sensitivity and stability at room temperature with a relative humidity of ~50%.